Measure for measure - Gupta, Amlan Das. ([S.l.] : Orient BlackSwan, 2004)
This edition of Measure for Measure is an annotated text with detailed notes on the play from different angles. It has a general introduction by the series editor and an introduction to the play by the editor of the book, marking the place of the play in Shakespeare's dramatic career. There is also a detailed analysis of each act so that the student will get a clear idea of the development of the plot structure. There is also an elaborate discussion of the different themes and ideas in the play and write-ups of the stage history and the sources of the play. There are line references, explanations and commentary which will enable the student to master the play. Cross-references which have been added on at all relevant points give the student a holistic view of the play. There is a list of further reading and a list of topics for discussion at the end of the edition.